PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI PADA DINAS PERHUBUNGAN KOTA LUBUKLINGGAU - Hardi Mulyono; Kabul Mika Arianto (Jurnal Interprof, 2021)
The study was conducted on the transport service of the city of lubuklinggau, with the purpose of the study to know how the environment affected workers' performance. The organizational culture of the environment in the city transport service office of lubukl ınggau research uses a saturated sample with 54 people sample workers in the city transport service to lubuklınggau as research respondents. Methods of data collection on this study are conducted by conducting interviews, observation, documentation, and questionnaires. The study suggests that the work environment affects significantly the development of Performance employees with organized culture as moderate variables has been suggested that the work environment is partially affected by Employee clarity's performance by 0363 or 36.39 and the organization's culture as moderated variables reinforces the working environment relationship to an employee's performance with r square 0.675 or 67,5% May conclude that the work environment Affected the performance of employees on the transport service of the city of lubuklinggau, then after being moderated by the organizational culture, resulted ina significant increase in Performance employees.